Pemodelan dan Optimalisasi Kinerja Jaringan Perpipaan Sistem Distribusi Air Bersih Menggunakan Epanet 2.2 (Studi Kasus: Desa Sumberejo, Kabupaten Madiun) - Raden Kokoh Haryo Putro; Alvia Nuriati Ramadhani (Prosiding ESEC, 2023)
The need for water must be directly proportional to the supply of clean water. The government through PERUMDA Drinking Water through the Sustainable Development Goals (SDGs) program in point six regarding clean water and adequate sanitation is trying to meet the target by 2030. In the distribution of clean water, the hydraulic system is an important aspect because flow and pressure influence the continuity of the hydraulic system. happen. This research was carried out using a quantitative analysis method with a case study of the distribution network development project carried out by PERUMDAM Tirta Dharma Purabaya in Sumberejo Village. Distribution network modeling was carried out using EPANET v.2.2 software to analyze discharge, flow velocity, pressure and pressure loss in the distribution network system on an ongoing basis for the next 10 years as well as evaluating and optimizing the water sources that will be used. Based on the EPANET v.2.2 simulation results in 2022, it shows that there are 24 pipes with problematic speeds, 21 junctions with problematic pressures, and 3 pipes with problematic headloss gradients. So recommendations for improving the distribution network in Sumberejo Village are made in accordance with the planning criteria of Minister of Public Works Regulation Number 27 of 2016 to optimize the performance of the distribution system for the next 10 years. The maximum head loss in the distribution network in 2022 will be 14.26 m/km and improvements are recommended so that by 2032 it will be 7.10 m/km.